2020
DOI: 10.2217/cer-2019-0193
|View full text |Cite
|
Sign up to set email alerts
|

Use of hyperbaric oxygen in hematopoietic cell transplantation to aid post-transplant recovery

Abstract: In this future pilot clinical trial concept patients will receive HBO therapy not only before stem cell infusion, but also afterward. In a separate approach, we are working on developing EPOR small-molecule inhibitors. "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…However, researchers have been developing strategies to increase the number of hematopoietic stem cells in UC units either in vivo or ex vivo (11). Preclinical experiments demonstrated that hyperbaric oxygen (HBO) treatment before the HSCT could improve homing of HSC in vivo during the transplant process and speed up neutrophil and platelet engraftment, reducing the risk of infections and bleeding during the critical period early post-HSCT (12,13). The same technique can be applied in autologous hematopoietic stem cell transplant with the intent to improve engraftment and to decrease hospitalization length.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have been developing strategies to increase the number of hematopoietic stem cells in UC units either in vivo or ex vivo (11). Preclinical experiments demonstrated that hyperbaric oxygen (HBO) treatment before the HSCT could improve homing of HSC in vivo during the transplant process and speed up neutrophil and platelet engraftment, reducing the risk of infections and bleeding during the critical period early post-HSCT (12,13). The same technique can be applied in autologous hematopoietic stem cell transplant with the intent to improve engraftment and to decrease hospitalization length.…”
Section: Introductionmentioning
confidence: 99%